The influence of sport goggles on visual target detection in female intercollegiate athletes - Kauffman, D. C.; Clark, J. F.; Smith, J. C. (Journal of Sports Sciences, 2015)
The aim of this study was to examine the effects of sport goggles on visual target detection in female intercollegiate athletes. Participants were randomly divided into three groups that varied in goggle use (G) or no goggle use (NG) over a total of three 1-min trials during a visual target detection task. The NG-NG-NG group did not wear goggles for any of the trials, whereas the NG-G-NG group wore goggles for the second trial only, and the G-NG-G group wore goggles for the first and third trials. The task consisted of illuminated targets arranged in five concentric rings from central to peripheral visual angles. The effects of sport goggles on response time to detect targets were most evident in the peripheral rings. Those who did not wear sport goggles showed improved performance from the first to second trials. This improvement was impaired, however, in those who wore sport goggles. Moreover, there was a reversal of the performance improvements achieved without goggles in those who wore goggles on the third trial. Together, these findings suggest the sport goggles not only impaired the expected initial performance but also impaired visual target detection after performance improvements were seen. These findings suggest sport goggles may impair detection of peripheral visual stimuli in athletes.